Optimalisasi Proses Rekrutmen Dan Seleksi Guru Di Lembaga Pendidikan - Ariana Ariana; Rahmatun Nisa; Hasyim Basid; Tengku Darmansah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The recruitment and selection process of teachers in educational institutions plays a crucial role in determining the quality of education provided to students. In the context of an ever-evolving education system, the challenges of finding competent educators have become increasingly complex. Various studies indicate that effective recruitment can contribute to the enhancement of teaching and learning quality. Therefore, optimizing this process is essential to meet the demand for quality education. This research aims to explore and analyze optimal strategies in the recruitment and selection process of teachers based on a literature review of related books and journals. By understanding existing best practices, this study is expected to provide recommendations that can be implemented by educational institutions to improve the effectiveness of their recruitment and selection processes. The methodology used in this research is a qualitative approach with a literature analysis. Data were collected through a systematic review of books and journals discussing teacher recruitment and selection. The analysis process involved identifying key themes emerging from various sources, as well as comparing and contrasting findings from existing literature to gain a comprehensive understanding of effective practices. The findings of this study indicate that the optimization of the teacher recruitment and selection process can be achieved through several strategies, including the use of more objective assessment tools, the development of clear selection criteria, and community involvement in the recruitment process. Additionally, this research also highlights the importance of training for selection committees to enhance their ability to assess teacher candidates holistically. The recommendations generated from this study are expected to contribute positively to educational institutions in their efforts to improve the quality of educators.